2022
DOI: 10.3390/molecules27103170
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Soft Tissue Extract from the Garden Snail Helix aspersa (Gastropoda, Mollusca)

Abstract: Gastropods comprise approximately 80% of molluscans, of which land snails are used variably as food and traditional medicines due to their high protein content. Moreover, different components from land snails exhibit antimicrobial activities. In this study, we evaluated the antifungal activity of soft tissue extracts from Helix aspersa against Candida albicans, Aspergillus flavus, and Aspergillus brasiliensis by identifying extract components using liquid chromatography-tandem mass spectrometry (LC-MS-MS). Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…54 Bioactive compounds extracted from H. aspersa soft tissue demonstrated strong antifungal effects against C. albicans, Aspergillus f lavus, and Aspergillus brasiliensis. 55 Liquid chromatography−mass spectrometry identified metabolites, including flavonoids, fatty acids, and steroids, as antifungal agents within the snail extracts.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
See 1 more Smart Citation
“…54 Bioactive compounds extracted from H. aspersa soft tissue demonstrated strong antifungal effects against C. albicans, Aspergillus f lavus, and Aspergillus brasiliensis. 55 Liquid chromatography−mass spectrometry identified metabolites, including flavonoids, fatty acids, and steroids, as antifungal agents within the snail extracts.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
“…Further chemical analyses identified antimicrobial metabolites, including glycosaminoglycans, achasin, acharan sulfate, and beta-agglutinin, exhibiting potent antibacterial effects against Enterococcus foecalis , one of the bacteria responsible for causing periodontitis . Bioactive compounds extracted from H. aspersa soft tissue demonstrated strong antifungal effects against C. albicans , Aspergillus flavus , and Aspergillus brasiliensis . Liquid chromatography–mass spectrometry identified metabolites, including flavonoids, fatty acids, and steroids, as antifungal agents within the snail extracts.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
“…Gallerimycin, isolated from the greater wax moth larvae Galleria mellonella, exhibited activity against A. niger , while ant-derived actinobacterial isolates showed an inhibitory capability against R. solani or Alternaria solani [ 146 , 148 ]. Hoda et al [ 149 ] reported the activity of extracts (methanolic, acetic acid, and acetone) from the snail Helix aspersa against A. flavus and Aspergillus brasiliensis in a concentration-dependent manner. Chromatographic analysis of these extracts showed that they contained phenolic compounds with antimicrobial properties including hesperidin, genistein, and luteolin, which are characterized by a wide antimicrobial potential [ 149 , 150 , 151 , 152 ].…”
Section: Animal-derived Antifungal Agentsmentioning
confidence: 99%
“…Hoda et al [ 149 ] reported the activity of extracts (methanolic, acetic acid, and acetone) from the snail Helix aspersa against A. flavus and Aspergillus brasiliensis in a concentration-dependent manner. Chromatographic analysis of these extracts showed that they contained phenolic compounds with antimicrobial properties including hesperidin, genistein, and luteolin, which are characterized by a wide antimicrobial potential [ 149 , 150 , 151 , 152 ]. The research described by Ulagesan and Kim [ 20 ] indicated that of the seven different snail proteins, the snail Cryptozona bistrialis proteins exhibited the most effective activity against A. fumigatus and P. chrysogenum .…”
Section: Animal-derived Antifungal Agentsmentioning
confidence: 99%
“…GN supplements are on the market particularly in Asia due to their health promoting effects. Evidence is piling up that GN has anti-inflammatory ( 6 ), anticancer ( 7 , 8 ), anti-diabetic ( 9 ), anti-hyperlipidemic ( 10 ), antiviral ( 8 , 11 ), antimicrobial ( 12 ), antifungal ( 13 ), cardioprotective ( 2 , 14 ), nephroprotective ( 15 ), antioxidant ( 16 , 17 ), and anti-obesity ( 18 ) properties among others. Surprisingly, recent studies revealed that GN is a potential endocrine disruptor (ED) that interferes with estrogen receptors (ERs) hence interfering with the endocrinology system ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%